2004
DOI: 10.1097/01.alc.0000122106.84718.67
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Brief Interventions for Hazardous Drinkers in Primary Care: Systematic Review and Meta‐Analyses

Abstract: Our results, although indicating smaller effect sizes than previous meta-analyses, do support the moderate efficacy of BIs. Further research is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
163
0
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(183 citation statements)
references
References 33 publications
5
163
0
12
Order By: Relevance
“…Alcohol SBI has been shown to be effective at reducing hazardous drinking in numerous effi cacy studies (e.g., Babor and Higgins-Biddle, 2001;Babor et al, 2006Babor et al, , 2007Ballesteros et al, 2004;Bien et al, 1993;D'Onofrio and Degutis, 2002;Moyer et al, 2002;Wallace et al, 1988;Whitlock et al, 2004;WHO Brief Intervention Study Group, 1996;Wilk et al, 1997). The widespread dissemination of SBI and SBIRT has received considerable policy support in the United States.…”
Section: S Creening and Brief Intervention (Sbi) Formentioning
confidence: 99%
“…Alcohol SBI has been shown to be effective at reducing hazardous drinking in numerous effi cacy studies (e.g., Babor and Higgins-Biddle, 2001;Babor et al, 2006Babor et al, , 2007Ballesteros et al, 2004;Bien et al, 1993;D'Onofrio and Degutis, 2002;Moyer et al, 2002;Wallace et al, 1988;Whitlock et al, 2004;WHO Brief Intervention Study Group, 1996;Wilk et al, 1997). The widespread dissemination of SBI and SBIRT has received considerable policy support in the United States.…”
Section: S Creening and Brief Intervention (Sbi) Formentioning
confidence: 99%
“…There is a large body of evidence highlighting the successful use of BIs, 11,12 with some authors suggesting reduction in alcohol consumption for periods of six up to 48 months. 13,14 Indeed a recent article proposed that the clinical relevance of alcohol BI is such that delaying dissemination will result in otherwise avoidable deaths.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis of PHC studies, it was found that treatment of 10 (95% CI 7 Á/17) hazardous drinkers was needed to obtain one success, i.e. reduced alcohol intake to moderate levels [14]. Studies have shown that the positive effect of a BI session is sustained for at least two years [17,18] and that conducting BI is cost-effective [19].…”
mentioning
confidence: 99%